Exploring experiences, perspectives, and the effect of flood disaster on food security among post-flood victims in Dun Guai Bera Pahang, Malaysia / Farihatun Najihah Abdul Khalib - Abdul Khalib, Farihatun Najihah (2016)
Flood disaster becoming the threat to property and safety of human population. Food security refers to the availability and accessibility to food, acquired in an acceptable means at any given time and place in a way that aids to sustain health and well being. There have been many study discovered that post flood victims faced negatives impact of food security on household and individual level since floods had negatively impacted household food stocks and daily livelihood activities. The degree to which specific characteristics of built environment affect the level of damage sustained by a community, in the context of food security has never been deeply studied and investigated in our population. Hence, the purpose of this study is to explore the experiences, perspectives and to identify the effect of flood disaster on food security among post-flood victims in Dun Guai Bera Pahang, Malaysia. The mixed method was conducted for this study. Based on the quantitative study, the cross-sectional study by using the questionnaire of demographic, and food consumption score survey were conducted to determine the effect of flood disaster on food security. The qualitative study was conducted through an in—depth interview in order to explore the food insecurity experiences and perspectives after the flood disaster. The total of 210 respondents takes part in the quantitative study while about ten participants take part in the in-depth interview. The data collected were analyzed based on thematic analysis by the aids of ATLAS.ti version 7.0 for Windows for qualitative study while the Food Consumption Score (FCS) and soda-demographic data were analyzed by the SPSS. Based on the quantitative study, the mean of the food consumption for all household was 63.96 which was in acceptable threshold level. Majority of the respondent were identified as acceptable diet (FCS > 35) with (n=209, 99.5%) and only (n=1, 0.5%) of the respondent was identified as poor diet (FCS = 0-21). Based on the qualitative study, 5 themes were recognized for this qualitative study. The five themes included quantity components, quality components, accessibility, psychological components, and flood aid management. This study findings hopefully able to help policy makers to find the solution to minimize the food insecurity problem, if any in higher education system